India's north-east: Government without governance - Bagai, Anita (2016)
India's North-East has been in the throes of conflicts that are myriad and multiple in nature-between the state and the social groups, among different ethnic groups as well as between the Union and the state governments. The region is in a state of uneasy quiet punctuated by sporadic disturbances. One of the critical reasons is disruption of governance. Clearly the institutions of governance have failed to provide socio-economic and political opportunities to its people thereby accentuating the problem of political alienation and conflict. The article attempts to look into the roots of the growing problems of governability; analyses the discourses of governance initiatives by the various governments; their failure to negotiate the embedded ideas of community; and concludes by establishing that peace and stability can be brought only by restoring governance and a liberal sharing of space and rights. - Reproduced.
Keywords: Public administration - India, North East; Public administration